Archetypal Images and Media Imaginary: potential and limitations of superheroic Great Mothers. - Bartoletti, Roberta (Italian Sociological Review, 2026)
This contribution falls within the field of cultural studies on media narratives, which are addressed from an original and still underexplored perspective. Cultural studies have typically examined how the media imaginary is shaped by hegemonic rhetorics, reproducing inequalities and rendering marginalized subjects and claims invisible. Within this framework, feminist cultural studies have analyzed representations of female agency across different media genres, which today are strongly influenced by postfeminist and neoliberal rhetorics. We propose to integrate the perspective of the archetype into the critical analysis of media narratives, as it allows for a deeper understanding of their symbolic efficacy—that is, their capacity to symbolically nourish the experiences of their audiences. Archetypal images are indeed powerful symbols, as they reveal the affective link between the embodied and “lived” symbol, and the symbol as represented in the collective imaginary. The study is based on a textual analysis of female superhero figures that may constitute contemporary actualizations of the archetypal images of the Great Mother within a transmedia corpus of North American superhero comics and films. The research question addresses the potentials and the limitations of these representations of female power and agency. The analysis first discusses how the superhero universe has ambiguously reconfigured female power, which is acknowledged yet continuously constrained within contemporary narratives; second, it shows that even a particularly challenging figure, such as the Dark Phoenix, fails to offer a significantly alternative imaginary of female power, thus highlighting persistent symbolic limitations even in current media representations regarded as progressive.